THE ROLE OF MADRASAH COMMITTEES IN SUPPORTING BOS FUND MANAGEMENT: CASE STUDY IN MADRASAH ALIYAH - Muslim, Bukhori; Marzuki, Ismail (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research examines the role of the Madrasah Committee in supporting the management of School Operational Assistance Funds (BOS) at Madrasah Aliyah Miftahul Ulum, Banyuanyar Lor, Gending, Probolinggo. The Madrasah Committee as a strategic partner of educational institutions has the responsibility to support the planning, implementation and supervision of the management of BOS funds in a transparent and accountable manner. This research uses a qualitative method with a case study approach, involving in-depth interviews with Madrasah Committee members, madrasah heads, teachers, as well as document analysis related to the management of BOS funds. The research results show that the role of the Madrasah Committee includes contributing to budget planning, providing strategic input on priority use of funds, as well as monitoring the implementation and reporting of BOS funds. However, several obstacles were found, such as committee members' limited understanding of fund management regulations and a lack of active participation in the evaluation process. To increase the effectiveness of the role, it is recommended that there be training and technical assistance for committee members, as well as strengthening synergy between the madrasah and the committee. These findings provide important insight into the importance of Madrasah Committee involvement in managing BOS funds to support improving the quality of education.